Supporting Breastfeeding Physicians Across the Educational and Professional Continuum: A Call to Action. (22nd December 2022) - Ortiz Worthington, Rebeca; Adams, Dara R.; Fritz, Cassandra D.L.; Tusken, Megan; Volerman, Anna
Abstract : The benefits of breastmilk and lactation are well established for both infants and women. National organizations recommend exclusively breastfeeding for the first 6 months of life and continued breastfeeding for the first 1–2 years of life. For physicians, childbearing years often coincide with key periods of training and their early career. Physician mothers have high rates of initiating breastfeeding but low success in maintaining breastfeeding. Breastfeeding discontinuation among physicians is a well-described, multifactorial issue that has persisted for decades. Reasons for discontinuation include inadequate access to pumping rooms, insufficient workplace and coworker support, and constrained schedules. Pumping is viewed as a burden to teammates and superiors, and physicians are often required to make up time spent pumping. Vague or absent policies to support breastfeeding by accreditation organizations and institutions create workplace conflict and impose additional stress on breastfeeding physicians, who devote significant time, energy, and mental reserves navigating clinical responsibilities, workplace relationships, and licensing requirements to pump. The authors propose several recommendations to improve the environment, support, and resources for breastfeeding physicians with a focus on what individuals, institutions, and professional organizations can do. Creating lactation policies that allow breastfeeding physicians equitable participation in the workplace is a matter of reproductive justice. Improving the collective awareness and support for breastfeeding trainees and physicians is a critical step in recruiting, retaining, and supporting women in medicine.